Analisis Permintaan Belanja Online di Indonesia - Alvinndo Ichwan Jati; Dian Isnawati; Wahyu Lestari (Inspirasi Nusantara, 2023)
The era of the digital economy has penetrated and changed people's lifestyles, one of which is the ease of transacting online. Gadget users increase every year and are offset by increasing e-commerce activities, this is indicated by the projected increase in e-commerce transactions. Since 2018 it has been recorded that Indonesian people make online shopping transactions through social media platforms, namely Facebook, Facebook Messenger, Instagram, and WhatsApp. In 2020, people have used various applications for online shopping such as Shopee, Tokopedia, etc. The demand for online shopping is increasing because people's income is increasing. Another cause is price changes that often go down due to discounts and price differences for online stores which tend to be cheaper than offline stores. Differences in brands or types cause everyone's tastes to be different so that it affects the demand for goods online. Unexpected expectations cause people to shop online to be one solution, namely when facing the Covid-19 pandemic, people tend to choose online shopping to avoid the virus. This study uses a literature review and results that income, changes and differences in prices, tastes, and expectations of a situation will encourage people's online shopping in Indonesia to increase.